P2X7 receptor-mediated analgesia in cancer-induced bone pain. (16th April 2015) - Falk, S.; Schwab, S.D.; Frøsig-Jørgensen, M.; Clausen, R.P.; Dickenson, A.H.; Heegaard, A.-M.
Highlights: P2X7R antagonisms could be a new advantageous target for the treatment of cancer-induced bone pain. P2X7R antagonism reduced neuronal responses in the dorsal horn. P2X7R antagonism reduced pain behavior in awake animals, without affecting motor coordination. P2X7R antagonism has no effect in naïve or sham animals, suggesting a state-dependent effect. The analgesic effect was not associated with increased expression of P2X7R in the spinal cord. Abstract: Pain is a common and debilitating complication for cancer patients significantly compromising their quality of life. Cancer-induced bone pain involves a complex interplay of molecular events, including mechanisms observed in inflammatory and neuropathic pain states, but also changes unique for cancer-induced bone pain. The P2X7 receptor (P2X7R) is involved in a variety of cellular functions and has been linked to both inflammatory and neuropathic pain. Here we study the analgesic potential of P2X7R antagonism in a rat model of cancer-induced bone pain. In cancer-bearing animals, the P2X7R antagonist A839977 attenuated dorsal horn neuronal responses in a modality and intensity-specific way. Spinal application of 0.4-mg/kg and 1.2-mg/kg A839977 significantly reduced the evoked responses to high-intensity mechanical and thermal stimulation, whereas no effect was seen in response to low-intensity or electrical stimulation. In contrast, A839977 had no effect on the tested parameters in naïve or sham animals. In awake animals, 40-mg/kg A839977 (i.p.) significantly reduced both early- and late-stage pain behavior. In contrast, no effect was observed in sham or vehicle-treated animals. The results suggest that the P2X7R is involved in the mechanisms of cancer-induced bone pain, and that P2X7R antagonism might be a useful analgesic target. No effect was observed in sham or naïve animals, indicating that the P2X7R-mediated effect is state-dependent, and might therefore be an advantageous target compared to traditional analgesics.